1998
DOI: 10.1083/jcb.140.3.485
|View full text |Cite
|
Sign up to set email alerts
|

Green Fluorescent Protein (GFP)-tagged Cysteine-rich Domains from Protein Kinase C as Fluorescent Indicators for Diacylglycerol Signaling in Living Cells

Abstract: Cysteine-rich domains (Cys-domains) are ∼50–amino acid–long protein domains that complex two zinc ions and include a consensus sequence with six cysteine and two histidine residues. In vitro studies have shown that Cys-domains from several protein kinase C (PKC) isoforms and a number of other signaling proteins bind lipid membranes in the presence of diacylglycerol or phorbol ester. Here we examine the second messenger functions of diacylglycerol in living cells by monitoring the membrane translocation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
242
1
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 316 publications
(256 citation statements)
references
References 45 publications
(62 reference statements)
9
242
1
4
Order By: Relevance
“…A small but functionally significant portion of RasGRP could be transiently recruited to the plasma membrane during the very brief period of diacylglycerol accumulation there following serum stimula- tion (42,48) and thus could be transiently brought in contact with plasma membrane-localized Ras GTPases. It should be noted that immunofluorescence studies of Sos1 and RasGRF-2 in serum-stimulated or ionophore-stimulated cells show predominant cytoplasmic distribution, with no detectable concentration at the plasma membrane (2,21), despite the evidence that these stimuli cause translocation of these GEFs to particulate fractions of the cell and stimulate GTP loading of Ras.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small but functionally significant portion of RasGRP could be transiently recruited to the plasma membrane during the very brief period of diacylglycerol accumulation there following serum stimula- tion (42,48) and thus could be transiently brought in contact with plasma membrane-localized Ras GTPases. It should be noted that immunofluorescence studies of Sos1 and RasGRF-2 in serum-stimulated or ionophore-stimulated cells show predominant cytoplasmic distribution, with no detectable concentration at the plasma membrane (2,21), despite the evidence that these stimuli cause translocation of these GEFs to particulate fractions of the cell and stimulate GTP loading of Ras.…”
Section: Discussionmentioning
confidence: 99%
“…phorbol ester (47,48). In addition to the histidines and cysteines required for zinc coordination, the C1 domain of mRas-GRP contains appropriate residues at the 11 positions that participate in forming a phorbol ester-binding pocket in the second C1 domain of PKC-␦ (64) (Fig.…”
Section: Selection Of a Cdna Clone Which Causes Ras-like Transformatimentioning
confidence: 99%
“…Fig. 3C shows the increase in a 2 as a function of time (t) that was used to calculate the diffusion coefficient (slope ϭ 4D) of YFP-STIM1 under the basal condition (25). The average apparent diffusion coefficients of YFP-STIM1 were Ϸ0.1 and 0.05 m 2 /s before and after ER Ca 2ϩ depletion, respectively (Fig.…”
Section: A Mutant Stim1 That Lacks the C-terminal Polybasic Motif Sepmentioning
confidence: 99%
“…3B). This result indicates that the distance of recruitment for STIM1 puncta formation is Ͻ5 m. To determine the average distance over which STIM1 is recruited to ER-PM junctions, we measured the apparent diffusion coefficient (D) by fitting the two-dimensional relative fluorescence intensity profiles (I) to a Gaussian function, I ϭ exp (Ϫ(x 2 ϩ y 2 )/a 2 ) and calculating the increase in the square of the Gaussian peak radius (a 2 ) as YFP-STIM1 diffused back into the bleached area (25). Fig.…”
Section: A Mutant Stim1 That Lacks the C-terminal Polybasic Motif Sepmentioning
confidence: 99%
“…Upon stimulation, the enzyme adopts an open conformation whereby intramolecular interactions are interrupted and binding sites for intermolecular interactions that stabilize the open form are exposed, resulting in a catalytically active enzyme. In the case of PKC, these intermolecular interaction sites are the binding sites for phospholipids and anchoring proteins (27,28). We have previously suggested that one intramolecular interaction in ⑀PKC that maintains the enzyme in a closed form is between an ⑀RACK-binding site and a ⑀RACK site (17).…”
Section: Mathematical Modeling Of ⑀Pkc Translocation Suggests That ⑀Pmentioning
confidence: 99%